THE EFFECT OF INFORMATION BOOKLET ON THE PATIENTS COMPLIANCE WITH ORAL ANTIBIOTIC COURSE IN SEVERAL COMMUNITY HEALTH SERVICE - Ilil Maidatuz Zulfa; Widya Handayani (Jurnal Farmasi Sains dan Praktis, 2021)
Inappropriate use of oral antibiotics will contribute to an increase in antibiotic resistance and treatment failure. Compliance with the use of oral antibiotics is one of the things that contributes to the inappropriate use of antibiotics. This study aims to analyze the effect of information booklet reminder media on adherence to short-term antibiotic use conducted in four puskesmas in the Surabaya area. Patients aged 19-50 years who were prescribed short-term antibiotics (<7 days) were included in this study. Patients were then grouped into two groups, namely the intervention group who was given an information booklet, and the control group. Compliance with the use of antibiotics was measured based on the calculation of the remaining antibiotics on the day the antibiotics ran out. A total of 192 people were recruited in this study, 96 people were in the intervention group and 96 people were in the control group. The results of measurement of adherence and analysis showed that 80.21% of patients in the intervention group were obedient in using their antibiotics, while patients in the control group were compliant with 60.42% (p-value 0.003). Based on these results, information booklets can significantly affect patient compliance in the use of short-term oral antibiotics so that information booklets can be used as one of the educational media in increasing adherence to antibiotic use.